The Development of Environmental Education Based on Ecoliteracy Module to Improve Global Perspective Ability on Students of Social Studies Education - Noverita, Anisa; Darliana, Eka; Siregar, Zulham (Budapest International Research and Critics University, 2021)
This study aims to overcome spatial inequality through learning that raises awareness of the importance of the environment in Social Studies Study Program students at STKIP Al Maksum Langkat. Ecoliteracy education illustrates awareness of the importance of the environment. Ecoliteracy level is an achievement where someone is very aware of the importance of the environment, the importance of maintaining and caring for the earth, ecosystems, nature as a place to live and develop life. This research uses research and development (R&D) type. The development research that will be carried out by the researcher is to design a product in the form of a module as a learning resource for social studies education students, then validate the module product. The population used in this study are students of the Social Studies study program, STKIP Al Maksum Langkat. From this population, two classes will be randomly selected to be used as research samples. The research is conducted from January to December 2021. The data analysis of textbook validation consisted of: (1) Finding the average per criterion, (2) Finding the average of each aspect, Research summary of no more than 500 words containing the research background, objectives and stages of research methods, targeted outputs, and descriptions of the proposed research TKT. (3) find the average total validity of all aspects. The practical analysis of the module consists of student responses and student activities, while the module effectiveness analysis only uses student learning mastery. Then the module analysis consists of: (1) Validity, (2) Difficulty Level, (3) Distinguishing Power and (4) Reliability. The outputs in this study consist of mandatory outputs and additional outputs, the mandatory outputs are internationally accepted while the additional outputs are textbooks with ISBN. For Technology Readiness Level between level 1 and level 2 only.